2019
DOI: 10.1007/s00401-019-02007-x
|View full text |Cite
|
Sign up to set email alerts
|

Binding of α-synuclein oligomers to Cx32 facilitates protein uptake and transfer in neurons and oligodendrocytes

Abstract: The intercellular transfer of alpha-synuclein (α-syn) has been implicated in the progression of Parkinson’s disease (PD) and multiple system atrophy (MSA). The cellular mechanisms underlying this process are now beginning to be elucidated. In this study, we demonstrate that the gap junction protein connexin-32 (Cx32) is centrally involved in the preferential uptake of α-syn oligomeric assemblies (oα-syn) in neurons and oligodendrocytes. In vitro, we demonstrate a clear correlation between Cx32 expression and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
41
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 77 publications
(120 reference statements)
9
41
0
Order By: Relevance
“…Recent studies have shown that cell-to-cell spreading of the pathogenic protein aggregates is necessary for propagation of the diseases [94,95]. Heparan sulfate proteoglycans (HSPGs), a family of proteins containing one or more sulfated glycosaminoglycan (GAG) heparan sulfate (HS) have been shown to play an important role in cellular uptake of the aggregated proteins, such as fibrils of amyloid-β [96] and tau [97].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that cell-to-cell spreading of the pathogenic protein aggregates is necessary for propagation of the diseases [94,95]. Heparan sulfate proteoglycans (HSPGs), a family of proteins containing one or more sulfated glycosaminoglycan (GAG) heparan sulfate (HS) have been shown to play an important role in cellular uptake of the aggregated proteins, such as fibrils of amyloid-β [96] and tau [97].…”
Section: Discussionmentioning
confidence: 99%
“…To do this, we used well characterized iPSC-derived ltNES cells, which upon differentiation, are electrophysiologically mature and display mature neuronal markers [14][15][16][17][18][19][20][21] . Since Aβ oligomers are thought to be the most relevant aggregates in AD pathology, we challenged the differentiated neurons with 1 µM oAβ over 24 h to mimic the early phase of oAβ challenge, similar to previous studies 22,23,[26][27][28][29][30] . Previous studies have shown that concentrations of up to 3 µM oAβ 1-42 exist within neurons of the AD brain 31 , while the concentrations of oAβ used in this study may reflect those in the immediate vicinity of amyloid plaque cores, the so-called halo region 32,33 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition to neurons, microglia were also involved in the intercellular transmission of α-syn oligomers, by secreting oligomers through exosomes and inducing α-syn accumulation in neurons [ 76 ]. While the exact mechanism of α-syn oligomers intercellular transfer is unclear, the gap junction protein connexin-32 (Cx32) was proved to preferentially ingest α-syn oligomers in neurons and oligodendrocytes [ 77 ].…”
Section: Prion Principle Of α-Syn Oligomersmentioning
confidence: 99%